2006
DOI: 10.1105/tpc.105.038844
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Rice MYBGA and the Gibberellin Response Element Controls Tissue-Specific Sugar Sensitivity of α-Amylase Genes

Abstract: Expression of a-amylase genes during cereal grain germination and seedling growth is regulated negatively by sugar in embryos and positively by gibberellin (GA) in endosperm through the sugar response complex (SRC) and the GA response complex (GARC), respectively. We analyzed two a-amylase promoters, aAmy3 containing only SRC and aAmy8 containing overlapped SRC and GARC. aAmy3 was sugar-sensitive but GA-nonresponsive in both rice (Oryza sativa) embryos and endosperms, whereas aAmy8 was sugar-sensitive in embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
89
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 102 publications
(92 citation statements)
references
References 60 publications
0
89
2
1
Order By: Relevance
“…The callus-containing rice embryos were prepared and particlebombarded as described (Chen et al, 2006). The rice embryos were cobombarded with reporter, effector, and internal control plasmids at a ratio of 2:1:0.25.…”
Section: Rice Embryo Transient Expression Assaymentioning
confidence: 99%
See 4 more Smart Citations
“…The callus-containing rice embryos were prepared and particlebombarded as described (Chen et al, 2006). The rice embryos were cobombarded with reporter, effector, and internal control plasmids at a ratio of 2:1:0.25.…”
Section: Rice Embryo Transient Expression Assaymentioning
confidence: 99%
“…In general, sugars upregulate genes involved in biosynthesis, transport, and storage of reserves and cell growth and downregulate those associated with photosynthesis, reserve mobilization, and response to stresses (Graham, 1996;Koch, 1996;Ho et al, 2001). Studies with Arabidopsis thaliana and rice (Oryza sativa) have revealed intimate interaction between sugar and plant hormones, environmental stimuli, and metabolic signaling pathways (Sheen et al, 1999;Gibson, 2000;Smeekens, 2000;Coruzzi and Zhou, 2001;Gazzarrini and McCourt, 2001;Rolland et al, 2002Rolland et al, , 2006Hong et al, 2003;Chen et al, 2006). Despite extensive efforts in the identification of mutants defective in sugar responses (Sheen et al, 1999;Rolland et al, 2002Rolland et al, , 2006, the identity of essential components in the sugar signaling pathway, the detailed mechanism underlying sugar-regulated transcription, and how they regulate plant growth and development remain mostly unclear.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations